Can AI be a content generator? Effects of content generators and information delivery methods on the psychology of content consumers. (December 2020) - Kim, Jina; Shin, Soyeon; Bae, Kunwoo; Oh, Soyoung; Park, Eunil; del Pobil, Angel P.
Highlights: The potentiality of using artificial intelligence (AI) technologies in news contents is addressed. The experiments with a two (human vs. AI) and three (text vs. audio vs. video) were conducted. Based on the results, both implications in using AI technologies are presented. Abstract: Considering the rapidly improving technologies in artificial intelligence (AI), researchers in mass communication and journalism have paid attention to the use of AI technologies. However, there are still notable concerns about the particular use of AI technologies in this field. Put simply, can AI technologies reduce human tasks? In order to address this question, this study investigates the effects of content generators (human vs. AI) and information delivery methods (text vs. audio vs. video) on users' perceptions of content. The results indicate that the generators and methods play a notable role in eliciting greater quality, satisfaction, and readability of the content. Based on the findings, the implications are addressed.